2021
DOI: 10.1177/09544070211024083
|View full text |Cite
|
Sign up to set email alerts
|

An anti-lock braking system algorithm using real-time wheel reference slip estimation and control

Abstract: Knowledge of the tyre-road interface traction limit during braking of a road vehicle can drastically improve safety and ensure stable braking on varied road conditions. This study proposes an optimal reference slip algorithm that determines the road surface while the vehicle is braking, by implicitly tracking the traction limit. It presents wheel slip variance regulation as a potential approach towards reference wheel slip estimation for wheel slip regulation (WSR). The variance regulation approach computes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…When referring to the lateral "Stability indexes", for instance, yaw rate and sideslip angle, we can find the same trends with the aforementioned safety indexes as demonstrated in Figures 9,10,17,and 18. The RMSEs for yaw rate and sideslip angle improve about 67.6%, 29.5%, and 90.4%, 26.7% with respect to pure braking and static allocation in highway impact as shown in Table 4.…”
Section: Control Performance Verificationsupporting
confidence: 63%
See 1 more Smart Citation
“…When referring to the lateral "Stability indexes", for instance, yaw rate and sideslip angle, we can find the same trends with the aforementioned safety indexes as demonstrated in Figures 9,10,17,and 18. The RMSEs for yaw rate and sideslip angle improve about 67.6%, 29.5%, and 90.4%, 26.7% with respect to pure braking and static allocation in highway impact as shown in Table 4.…”
Section: Control Performance Verificationsupporting
confidence: 63%
“…These systems are proposed to prevent possible crashes or impacts and protect the drivers and passengers from injuries. A lot of vehicle dynamics control techniques are growing industrialised as mounted active safety systems [16], such as anti-lock braking system (ABS) [17], electronic stability control (ESC) [18], active front steering (AFS) [19], torque vectoring [20,21], active limited-slip differential [22] etc. These systems contribute a lot to decrease the fatalities and injuries in road accidents [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It is proven in many simulation and experimental works, the superiority of its performance compared to the standard PID control method in controlling various dynamical systems (Abdelmaksoud et al, 2021; Al-Mola et al, 2012a; Hewit and Burdess, 1981; Muniandy et al, 2015; Priyandoko et al, 2009; Varatharajoo et al, 2011). This strategy was used in ABS to control the optimum wheel slip value in order to prevent the wheel from being totally locked under adverse operating conditions (Gaurkar et al, 2022; Lutfi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On taking friction factors of straight roads with homogeneous surfaces, the ABS shows a reduction in the braking distance. It was observed that the reduction range in such situations was 7%-18% which was much better than wheels without ABS (Gaurkar et al, 2022). In another work, the hydraulic ABS system with an intelligent controller control braking was tried based on the real-time slip ratio of the wheels estimated from vehicle velocity.…”
Section: Introductionmentioning
confidence: 99%